Adaptive Climate Change Governance in Makassar, Indonesia - Zaldi Rusnaedy; Almuhajir Haris; Umar Congge; Andi Luhur Prianto (Journal of Governance, 2021)
Over the past few years, historical records show that floods and strong winds are climatic phenomena that always cause damage and loss to cities. To climate vulnerability and disasters, the geographical character of the city causes the types of vulnerability and the impact of disasters to vary widely. Due to the unpredictable nature of climate change, there is a need for intervention from government agencies through policies and governance to reduce risks from the impacts of climate change. Therefore, this study aims to analyze how the Makassar City Government carries out governance to adapt to climate change. The research method used is a qualitative method with data collection techniques through interviews and document review. This research shows that the Makassar government is to formulate seven strategies to reduce the impact of climate change, form a Climate Change Adaptation Working Group and make priority village programs. Priority village program policies will make it easier to map areas with high to low levels of exposure. So with this policy, Makassar will become a city that is more adaptive to climate change. We propose increasing adaptability and decreasing sensitivity to exposure so that Makassar residents will be more resilient in the face of future climate change. In addition, adaptation action does not only rely on the government. However, it involves the community and the private sector so that collective action is created in the context of adapting to climate change.